Evaluation of criteria for CO2 capture and storage in the iron and steel industry using the 2-tuple DEMATEL technique. (1st May 2016) - Quader, M. Abdul; Ahmed, Shamsuddin; Raja Ghazilla, Raja Ariffin; Ahmed, Shameem; Dahari, Mahidzal
Abstract: Nowadays, the development and deployment of alternative iron-making breakthrough technologies along with CO2 capture technology are receiving high priority to mitigate environmental concerns by reducing pollutants and greenhouse gas (GHG) emissions. During the joint selection and successful implementation of CO2 capture and storage (CCS) technology with iron-making emerging technology in order to allow the continuous use of fossil fuel as a reliable source of energy on demand, decision-makers (DMs) face different uncertainties and barriers as trade-off conditions in a real world environment. This study aims to quantitatively prioritize and analyze the interactions between the complex factors and dimensions in respect of CCS implementation in the iron and steel industry. In addition, research evaluates the CCS systems with twenty-five influential success factors in terms of four prominent aspects of sustainability, namely, engineering, economic, environmental and social. To carry out the research, this study utilizes the modified 2-tuple DEMATEL technique, a Multi-criteria Decision Making (MCDM) tool and the Delphi method by proposing a favorable framework to determine the cause-and-effect relationships among these criteria. The results show that the criteria of energy for capture and storage, and CO2 removal efficiency are the top two significant influencing factors in selecting CO2 capture technology with breakthrough iron-making technologies. In addition, an intelligent network relationship map among the dimensions and the overall DEMATEL prominence-effect relationship diagram between the cause group and effect group of criteria have been illustrated clearly. A case study was conducted in an iron and steel manufacturing industry in Malaysia to illustrate the proposed framework and to demonstrate its usefulness and validity. Highlights: A MCDM model has been proposed for CCS systems evaluation. Quantitatively prioritized and analyzed the critical success factors and dimensions. Feasibility and potentials of CCS technology deployment has been investigated. Surveys and case studies have been conducted to illustrate the proposed framework. Model shows favorable solution for solving decision problems in a real world environment.